Utilization of Financial Technology as a Source of Capital for Songket Craftsmen Group in Muara Penimbung Ulu, Ogan Ilir - Fida Muthia; Agil Novriansa; Asfeni Nurullah; Hasni Yusrianti (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
This community service aims to provide knowledge and understanding to songket craftsmen regarding the use of fintech as a source of capital. The implementation of this community service is carried out using two methods, namely focus group discussions (FGD) and training. The training was conducted using lecture, discussion and simulation methods. Evaluation of activities for participants is carried out by giving pre-test and post-test. Monitoring of service activities will also be carried out to see the progress of the implementation of the material presented. From the results of service activities in Desa Muara Penimbung Ulu, it is known that currently songket craftsmen are still experiencing capital difficulties due to problems with the documents needed to apply for a capital loan. The majority of songket craftsmen also do not understand how to use fintech as their source of capital. Therefore, holding training related to fintech is important to increase public understanding regarding how to use and utilize it.